Investigating the impact of wet rendering (solventless method) on PUFA-rich oil from catfish (Clarias magur) viscera - Jaydeep Dave; Ali Muhammed Moula Ali; Nishant Kumar; Muralidharan Nagarajan; Marek Kieliszek; Sri Charan Bindu Bavisetty (My University, 2024)
Abstract Catfish ( Clarias magur ) is a popular freshwater fish food worldwide. The processing of this fish generates a significant amount of waste, mainly in the form of viscera, which constitutes around 10–12% of the fish’s total weight. This study was focused on extracting polyunsaturated fatty acid (PUFA)-rich oil from catfish viscera, aiming to enhance the extraction process and make the production of oil and handling of fish byproducts more cost-effective. The wet reduction method, a solvent-free approach, was used for extraction, with yield optimization done via the Box–Behnken design. The resulting oil was evaluated for its oxidative quality and chemical characteristics. The optimal conditions for the wet rendering process were as follows: viscera to water ratio, 1:0.5 (w/v); temperature, 90℃; and time, 20 min, yielding 12.40 g/100 g of oil. The oil extracted under optimal wet rendering conditions had quality and oxidative stability comparable to solvent extraction and fewer secondary oxidation compounds. This oil had a higher PUFA content, specifically a 4:1 ratio of omega 6 to omega 3. Such oil, derived from catfish viscera, is suitable for the food industry due to its solvent-free extraction method.
Keywords: Clarias gariepinus; Clarias; Meat and Animal Product Quality